STRATEGIC HUMAN RESOURCE MANAGEMENT ISSUES AND THEIR INFLUENCE ON COMPETITIVE ADVANTAGE - Supardi; Ferdinandus Christian; Yuyunita (Adisam Publisher, 2026)
Strategic human resource management is crucial for gaining a competitive edge for organizations. There are several strategic issues that need to be considered in human resource management, namely organizations must be able to handle employee competency and manage conflicts at work. In order to compete in the global market, businesses must innovate to improve performance as the need to assess productivity grows market, the adoption of information technology must be integrated with organizational strategy. This is important so that technology can increase competitive advantage, not just as a stand- alone tool, The job of human resources is impacted by the constantly shifting business environment. Organizations must reorient human resources' competency and behavior to adapt to new challenges and increase competitiveness. Managing quality human resources is very important. An organization's competitive edge may benefit from effective human resource management. The organization's capacity to compete and endure in a cutthroat business environment is significantly impacted by problems with strategic human resource management.